CONCEPTUAL FRAMEWORK FOR APPLYING INTERNET OF THINGS IN PRODUCTION SYSTEMS FOR SENSING ENTERPRISES - Boza, Andrés; Cortes, Beatriz; Alemany, Maria del Mar Eva; Cuenca, Llanos (Brazilian Journal of Operations & Production Management, 2016)
Sensing Enterprise is a new concept, which appears with the Internet of Things (IoT) application in industry. This technology applied in production sys- tems provides many benefits like better transparency or real time information. This approach proposes a conceptual framework for IoT application in Production Systems. The aim of this framework is helping enterprises to identify the main el- ements to apply IoT in Production Systems. To create this framework, a literature review has been made and the main components of IoT in Sensing Enterprise in production proposals have been identify. Thus, these elements and its relations have been the source for the conceptual framework proposed.